Spatial analysis of learning results in high school mathematics and Polish by county. - Ejsmont, Wiktor; Łyko, Janusz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
One way to assess the quality of the educational activities of schools is to analyze the educational value-added, with the help of which it is possible to measure the gain in students‟ knowledge that takes place at various stages of education. This is an objective measurement that takes into account the knowledge with which the student begins the next stage of learning. Access to data on the final results of tests at every stage of education enables the assessment of the quality of education in schools throughout Poland. The article aims to analyze these results and attempts to show the spatial dependence of the results obtained.
Didactics of Mathematics, 2013, Nr 10 (14), s. 19-32
Keywords: educational value added; random effects model; taxonomy; development pattern; panel data